DIRECTIONS TO MITIGATE THE IMPACTS OF EXTREME DROUGHT ON CAIMANS (Caiman yacare) POPULATIONS IN THE PANTANAL - Campos, Zilca; Mourão, Guilherme; Muniz, Fábio de Lima; Maffei, Fábio [UNESP]; Botero-Arias, Robin; Magnusson, William Ernest (Oecologia Australis, 2022)
Global climate change has negative effects in different ways around the world, and in the Pantanal the extreme drought of the last three years seems to be one such scenario. Many aquatic or semi-aquatic species occur in the Pantanal due to a large availability of seasonally flooding habitats. In the 1990s, the population size of the Pantanal caiman, Caiman yacare, was estimated at around 3 million individuals, but at present, it faces a decline due to the water scarcity in the remaining rivers, lakes and water holes. The species responds to the droughts adopting survival strategies such as aestivation in the mud and in the interior of the forest. We recommend three general measures for the conservation of the Pantanal ecoregion and five specific management actions to minimize the effects of drought on caiman populations for the Pantanal.
DIREÇÕES PARA MITIGAR OS IMPACTOS DA SECA EXTREMA NAS POPULAÇÕES DE JACARÉS (Caiman yacare) NO PANTANAL
Keywords: Brazil; climate change; conservation; extreme drought; Pantanal caiman